Bioavailability of tomato polyphenols is enhanced by processing and fat addition: Evidence from a randomized feeding trial - Martínez-Huélamo, Miriam; Vallverdú-Queralt, Anna; Di Lecce, Giuseppe; Valderas-Martínez, Palmira; Tulipani, Sara; Jáuregui, Olga; Escribano-Ferrer, Elvira; Estruch, Ramón; Illan, Montse; Lamuela-Raventós, Rosa M. (Molecular nutrition & food research, 2016)
Scope Tomato contains a variety of phenolics associated with health‐promoting properties. However, the effects of processing and the addition of oil during tomato sauce preparation on microbial metabolism of phenolics in the small intestine are still unclear. Methods and results An open, controlled, randomized, and crossover feeding trial with 40 healthy volunteers was carried out to analyze the metabolites in plasma and urine after the consumption of tomato and tomato sauces, with tomato sauce enriched with refined olive oil (ROOE) and without refined olive oil (oil‐free: OF). Ten phenolics in plasma and 93 metabolites in urine were quantified. Processing tomatoes into sauce enhanced the bioavailability of flavanones, flavanols, and some hydroxycinnamic acids, as reflected by the increase in the area under the plasma concentration versus time curve. An increase in their plasma half‐life was also observed, particularly after ingestion of ROOE, possibly favored by enterohepatic circulation. A wide variety of gut microbial metabolites was also detected, namely flavanones, hydroxycinnamic acids, flavonols, hydroxyphenylpropanoic acids, hydroxyphenylacetic acids, and hydroxybenzoic acids. Conclusions Flavanones and flavonols in ROOE presented higher bioavailability, suggesting that the processing undergone by the raw tomato improved their absorption. In order to verify if the bioavailability of the phenolic compounds contained in tomato and tomato sauces is influenced either by the processing or the addition of a lipid matrix during sauce processing, we performed a prospective randomized, crossover study with 40 healthy volunteers and three interventions: raw tomatoes, oil‐free tomato sauce (OF), and refined olive oil‐enriched tomato sauce (ROOE). Processing tomatoes into sauce enhanced the bioavailability of flavanones, flavanols, and some hydroxycinnamic acids, particularly after ingestion of ROOE.